Hurricane Recovery and Ecological Resilience: Measuring the Impacts of Wetland Alteration Post Hurricane Ike on the Upper TX Coast. - Reja, Md; Brody, Samuel; Highfield, Wesley; Newman, Galen (Environmental Management, 2017)
Recovery after hurricane events encourages new development activities and allows reconstruction through the conversion of naturally occurring wetlands to other land uses. This research investigates the degree to which hurricane recovery activities in coastal communities are undermining the ability of these places to attenuate the impacts of future storm events. Specifically, it explores how and to what extent wetlands are being affected by the CWA Section 404 permitting program in the context of post-Hurricane Ike 2008 recovery. Wetland alteration patterns are examined by selecting a control group (Aransas and Brazoria counties with no hurricane impact) vs. study group (Chambers and Galveston counties with hurricane impact) research design with a pretest-posttest measurement analyzing the variables such as permit types, pre-post Ike permits, land cover classes, and within-outside the 100-year floodplain. Results show that permitting activities in study group have increased within the 100-year floodplain and palustrine wetlands continue to be lost compare to the control group. Simultaneously, post-Ike individual and nationwide permits increased in the Hurricane Ike impacted area. A binomial logistic regression model indicated that permits within the study group, undeveloped land cover class, and individual and nationwide permit type have a substantial effect on post-Ike permits, suggesting that post-Ike permits have significant impact on wetland losses. These findings indicate that recovery after the hurricane is compromising ecological resiliency in coastal communities. The study outcome may be applied to policy decisions in managing wetlands during a long-term recovery process to maintain natural function for future flood mitigation.